Challenges of Social Science Literacy - Birgit Weber (Journal of Social Science Education, 2010)
Since international tests compare the performance of students in different subjects, the issue of literacy in the social science subject is becoming more pressing. The successes and failures in international tests influence the national education policies considerably. First, the inclusion of subjects in international comparisons has consequences for their importance. Second, the race in the Olympics of education leads to an increasing focus on the output of educational processes, also measured in the central exams. Social Sciences can refuse to take part in the national comparison studies with the price of losing much more importance; they can participate with the danger of undermining their goals. This raises a lot of questions: What competences students need in this social world to reason about it und to act responsibly? What is the foundation of concepts from social science students need for guidance and understanding their place and role as an individual in society? The social science disciplines, as sociology, political science and economics in a narrow sense, history, law and geography in a broader sense, supported by philosophy, pedagogy and psychology are able to select them for educational purposes or determine such educational aims. This Journal wants to resume und discuss competences and core con¬cepts for political and economic teaching and learning as Social Science Literacy”. Contributions in this issue do not only discuss and recommend competences and core concepts from a domain specific political or economic point of view, but also from an interdisciplinary or psychological point of view. They analyse preconditions and interdependencies as well as obstacles und problems of development and diagnosis core concepts and competences of Social Science Literacy.